Class conflict and modernization in India : the Raj and the Calcutta waterfront ( - Aniruddha Bose (Routledge studies in south asian history, 2018)
In the days of the British Raj Calcutta was a great port city. Thousands of men, women, and children worked there, loading and unloading valuable cargoes that sustained the regional economy, and contributed significantly to world trade. In the second half of the nineteenth century, in response to a shift from sailing ships to steamers, port authorities in Calcutta began work on a massive modernization project.